Microscopic Study on the Diameter of the Parietal Cells of Post Mortem Human Stomach - Basak, Pran Krishna; Talukdar, Suchitra; Kabir, Md Ashraful; Kumar Barman, Biplab; Al Foysal, Abdullah; Suchi, Halima Akther; Sultana, Mahmuda; Biswas, Anup Kumar; Roy, Joyashish; Debnath, Joyanti Rani; et al. (Medicine Today, 2025)
Introduction: Disease pattern as well as diagnostic and treatment options may be helped by examining the diameter of parietal cells of human stomach, as the change with age. It seems that there is a few research in this area and needs more studies, including gross anatomical studies, with data available in Bangladesh. Materials and Methods: This Cross-sectional descriptive study was carried out at Department of anatomy, Sylhet M.A.G. Osmani Medical College, Sylhet during the periods from January 2013 to December 2013. Fifty human postmortem stomach were selected from unclaimed dead bodies that were under examination in the morgue of department of Forensic Medicine, Sylhet M.A.G. Osmani Medical College, Sylhet. The collected samples were divided into 3 groups upon age. Group A (7-14 years), Group B (15-22 years) and Group C (23-64 years). Histological study was carried out on relatively 18 fresh samples. Results: The mean diameter of parietal cells was 14.09(SD± 0.91) μm in the age group of 7 to 14 years ; 16.60 (SD± 0.91) μm in the age group of 15 to 22 years and 17.81(SD± 1.52) μm in the age group of 23 to 64 years (p˂0.001) with 16.69(SD± 2.03) μm in male and16.49(SD± 1.99) μm in female (p=0.825) A significant positive correlation was observed between age and diameter of parietal cells (p˂0.001). Conclusion: Age related changes were found in the diameter of parietal cells. Medicine Today 2025, Vol.37 (1): 108-110